A Phenylene‐Bridged Cyclohexa‐meta‐phenylene as Hexa‐peri‐hexabenzocoronene Precursor. Issue 46 (4th July 2018) - Dumslaff, Bastian; Wagner, Manfred; Schollmeyer, Dieter; Narita, Akimitsu; Müllen, Klaus
Abstract: A phenylene‐bridged cyclohexa‐ meta ‐phenylene was synthesized via intramolecular Yamamoto coupling of an appropriate p ‐quinquephenyl derivative carrying four m ‐chlorophenyl substituents. The structural proof could be obtained by single‐crystal X‐ray diffraction analysis, which also revealed a slightly strained structure with an internal phenylene bridge. Notably, this cyclo‐ meta ‐phenylene served as a novel precursor for hexa‐ peri ‐hexabenzocoronene (HBC). The cyclodehydrogenation proceeded smoothly, providing the corresponding HBC derivative as confirmed by MALDI‐TOF‐MS, and UV/Vis spectroscopy. Abstract : Phenylene is in a ring : A unique cyclohexa‐ meta ‐phenylene with an internal benzene‐bridge was synthesized and characterized. Planarization lead surprisingly smooth to its appropriate HBC, which could be monitored by MALDI‐ToF‐MS and UV/Vis.